Geological Filmmaking - Litvintseva, Sasha (MEDIA : ART : WRITE : NOW, 2022)
Every film image is geological. As a technical medium derived from the metals and minerals extracted from the earth, every moving image is materially embedded in the world it records. It is also temporally linked to the almost inconceivably vast deep time of the planet's formation. What would it mean to make films in response to this situation? Geological Filmmaking argues that the challenge lies in situating oneself in the space between the concrete object of a film and the broader planetary conditions of its existence. The nuances of this position are at once formal, ethical and political. Sasha Litvintseva discusses her process of developing such a film practice as a way of tackling the perceptual and aesthetic difficulties presented by ongoing ecological crises. These concerns are explored through the prism of the author's own films about asbestos and sinkholes in their respective economic and colonial contexts. Geological Filmmaking develops a new genre of writing rooted in a reciprocity between the practice of making films and the theoretical study of the relations they participate in. Litvintseva expands current conversations in the environmental humanities through building on the rich legacy of experimental film as a tool for producing alternative modes of experiencing the world. The book is intended for readers from a broad range of backgrounds, looking for new ways of dealing with questions about the life and death of our planet.